Electrocardiographic Assessment of National-Level Triathletes: Sinus Bradycardia and Other Electrocardiographic Abnormalities - Mike Climstein; Kenneth S. Graham; Michael Stapelberg; Joe Walsh; Mark DeBeliso; Kent Adams; Trish Sevene; Chad Harris (Sports)
Background: High-intensity endurance training induces specific cardiac adaptations, often observed through electrocardiographic (ECG) changes. This study investigated the prevalence of ECG abnormalities in national-level Australian triathletes compared to sedentary controls. Methods: A cross-sectional observational study was conducted involving 22 triathletes and 7 sedentary controls. Standard 12-lead ECGs assessed resting heart rate, ECG intervals, and axis deviation. Peak oxygen consumption was evaluated in triathletes to correlate with ECG indices and left ventricular mass, derived via echocardiography. Results: Triathletes exhibited significantly lower resting heart rates (53.8 vs. 72.1 bpm, −34%, p = 0.04), shorter QRS durations (0.088 vs. 0.107 ms, −21.6%, p = 0.01), and longer QT intervals (0.429 vs. 0.358 ms, +16.6%, p = 0.01) compared to controls. Sinus bradycardia was present in 68.2% of triathletes, with varying severity. First-degree atrioventricular block was identified in 13.6% of athletes, and left ventricular hypertrophy was confirmed in 18 triathletes via echocardiography. A significant positive relationship was identified between VO2peak and left ventricular mass (r = 0.68, p = 0.003). Conclusions: National-level triathletes exhibited ECG and structural cardiac adaptations consistent with high-intensity endurance training. Echocardiography is recommended for the accurate identification of LVH. These findings highlight the need for comprehensive cardiac evaluation in athletes to distinguish between physiological and pathological adaptations.